Challenges and opportunities in designing dementia‐friendly communities with local governments. (20th December 2022) - Karamacoska, Diana; Salunke, Pranal; Shatnawi, Eman; Caballero, Gabriela; Steiner, Genevieve Z.; Dadich, Ann; DiGiacomo, Michelle; Morrison, Nicky; Alliance, Canterbury‐Bankstown Dementia
Abstract: Background: Communities that do not accommodate the needs and preferences of people with dementia can exacerbate disability and isolation. Although dementia‐friendly communities (DFCs) were established to foster understanding and acceptance of dementia, the built environment remains underexplored. We identified the challenges and opportunities for fostering dementia‐enabling environments among community planners. Method: This study is set in South‐West Sydney, Australia, where a DFC is being established. The policies of seven local governments were analysed for actions that aligned with Dementia Australia's 41 DFC recommendations: 13 for social, 14 for outdoor, and 14 for indoor environments. An online workshop was then held with 30 community planners to raise awareness for dementia‐enabling environments. Participants were surveyed about their dementia beliefs and attitudes. Facilitated discussions identified challenges and opportunities for designing DFCs. Qualitative and quantitative data across all sources were triangulated. Result: Although none of the local government policies specifically mentioned dementia, up to 20/41 DFC actions were met. Most of these were in social engagement (with ≤10/13 recommendations met by each local government). Less action was taken on outdoor and indoor environments (with ≤9/14 outdoor and ≤4/14 indoor recommendations met by up to six local governments). Although beliefs and attitudes about dementia among planners were generally positive, only 48% indicated that they had a good understanding of it and nearly 80% noted they would feel anxious and depressed about a diagnosis. Key DFC challenges included a lack of awareness and conflicting priorities between government bodies. Opportunities included engaging with universities to conduct demographically relevant awareness raising, facilitate multisectoral collaboration, developing an evidence‐base, and involving service providers to engage with the dementia community. Conclusion: This study triangulated data to identify gaps in community planning efforts, confirming that more action is required to design dementia‐friendly communities. We are now leading a multisectoral collaboration to educate community planners and the public, and are advocating for the recognition of dementia‐friendly environments in government plans. This study provides practical guidance to assist planners with DFC designs.